2006
DOI: 10.1016/j.seizure.2005.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electroencephalographic study of first-degree relatives and probands with juvenile myoclonic epilepsy

Abstract: The incidence of different kinds of IGEs and typical EEG trait is high in first-degree relatives of JME probands. IGE features were noted in 61% of the families. JME is the most common type of IGE and IGE features were found to be more frequent among siblings than parents. These findings confirm familial susceptibility to IGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
(64 reference statements)
1
23
3
4
Order By: Relevance
“…Actually, different epileptic syndromes such as childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), or generalized tonic-clonic seizures only (GTCS) may be observed in members of the same family, thus suggesting that they are genetically related to JME and that the genetic alterations responsible for JME may also underlie these non-JME forms of GGEs. 2,4 In three multigenerational families parents had adult onset GGE, while in children an earlier age of seizure onset was observed. Larger study group is needed to clarify the possible explanation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, different epileptic syndromes such as childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), or generalized tonic-clonic seizures only (GTCS) may be observed in members of the same family, thus suggesting that they are genetically related to JME and that the genetic alterations responsible for JME may also underlie these non-JME forms of GGEs. 2,4 In three multigenerational families parents had adult onset GGE, while in children an earlier age of seizure onset was observed. Larger study group is needed to clarify the possible explanation.…”
Section: Resultsmentioning
confidence: 99%
“…Although concordance analysis demonstrated that there is greater clustering within families of GGE syndrome, seizure type and age at onset that would be expected by chance, 2 the phenotypic heterogeneity is common: numerous studies revealed that about 40% of the families probands and relatives has JME only, the others have members with additional forms of GGE. 3,4 Although the exact type of inheritance is currently not known, the rare family and genetic studies indicate rather contradictory modes: autosomal dominant, recessive, maternal or complex. 5,6 In this study, we evaluate clinical features of probands with JME and phenotypes of affected members of their families in order to study clinical genetics of JME.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the proportion of individuals with IGE who have affected relatives appears to be high (Marini et al, 2003; Jayalakshmi et al, 2006), one option is to concentrate on families that have phenotypic data available on more than one affected member. This would allow a greater understanding of the phenotypic effect of the pre-disposing genetic variant within that family.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies (Doose et al, 1973;Heijbel et al, 1975;Degen and Degen, 1990a;Degen and Degen, 1990b;Atakli et al, 1999;Serra et al, 2001;Jayalakshmi et al, 2006 SPSW: generalized >3-Hz spike or polyspike-and-slow waves, 3-Hz SW: 3-Hz spike-and-slow waves, CTS: centrotemporal sharp or spike waves. JME, CAE and RE: EEG of asymptomatic relatives Verrotti et al, 2013) were included in the meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%